Antiphospholipid Antibodies: Cognitive and Motor Decline, Neuroimaging and Neuropathology - Arvanitakis, Zoe (Neuroepidemiology, 2019)
BACKGROUND: Few data are available on associations of antiphospholipid antibodies (aPL) with cognitive and motor decline in aging, and cerebrovascular disease on in-vivo neuroimaging and postmortem neuropathology. METHODS: This longitudinal, clinical-pathologic study (Antiphospholipid antibodies, Brain Infarcts, and Cognitive and Motor decline in Aging: ABICMA), was derived from two ongoing community-based cohort studies. A panel of 3 antiphospholipid antibodies (aPL) were assayed in serum from 956 older individuals (mean age =81.1 years; 72% women). Serum was also tested, in a subset for markers of inflammation (C-reactive protein: CRP) and blood-brain barrier breakdown (matrix metalloproteinases, MMPs). Annual clinical evaluations documented cognitive (17 neuropsychological tests) and motor function including parkinsonism. Cerebrovascular disease data were derived from in-vivo neuroimaging and postmortem neuropathologic evaluations (699 individuals). We examined associations of aPL with cognitive and motor decline, other serum markers, neuroimaging, and neuropathology. RESULTS: Of 956 individuals, 197 (20.6%) had aPL positivity, defined as positivity on any of the assays, at the time of first measurement. During a mean follow-up 6.6 years (SD=4), overall aPL positivity was not associated with change in global cognition (estimate=−0.005, SE=0.011; p=0.622) or parkinsonian signs (estimate=−0.003, SE=0.017; p=0.860). aPL was not associated with serum CRP or MMPs (both p>0.268). aPL was not associated with in-vivo brain MRI white matter hyperintensities or infarcts (both p>0.376). Among those autopsied, aPL was not associated with pathologically-confirmed brain infarcts, or cerebral atherosclerosis or arteriolosclerosis (all p≥0.447). CONCLUSIONS: In older individuals followed longitudinally, aPL does not relate to cognitive or motor decline, inflammation, or cerebrovascular disease on in-vivo neuroimaging or postmortem neuropathology.